1990
DOI: 10.1002/j.1460-2075.1990.tb08088.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sequences responsible for positive and negative regulation by E1A in the promoter of H-2Kbm1 class I MHC gene.

Abstract: The mechanism of transcriptional regulation of the H‐2Kbm1 major histocompatibility complex (MHC) class I gene by adenovirus type 12 E1A (Ad12‐E1A) was studied in transfected rat embryonal fibroblasts. Results of long‐term expression of the chloramphenicol acetyl transferase (CAT) gene placed under the control of the 5′‐flanking region of the mouse MHC class I gene. H‐2Kbm1, and the results of nuclear run‐on transcription assays, yield evidence for both positive and negative regulation of H‐2Kbm1 by E1A gene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 44 publications
(32 reference statements)
2
32
0
Order By: Relevance
“…We have also found that constitutive ICS-binding activity is very low in the CNS (56). Additional regulatory elements present upstream from region I and downstream from the ICS have been reported (13,33,38,71). These studies have provided a foundation on which to further investigate the regulatory mechanisms of MHC class I gene expression.…”
supporting
confidence: 59%
“…We have also found that constitutive ICS-binding activity is very low in the CNS (56). Additional regulatory elements present upstream from region I and downstream from the ICS have been reported (13,33,38,71). These studies have provided a foundation on which to further investigate the regulatory mechanisms of MHC class I gene expression.…”
supporting
confidence: 59%
“…on the activity of CEA promoter in plasmid co-transfection experiments. Plasmid pGL3-CEApr, which carries the gene for firefly luciferase directed by the CEA promoter was provided by the RIKEN DNA Bank (Tsukuba, Ibaraki, Japan) and plasmid pE1A5.13S, 41 which carries the E1A-13S gene of Ad type 5, was provided by Dr Shiroki (Tokyo University, Tokyo, Japan). Plasmid pSV-b-galactosidase, which carries a gene for b-galactosidase directed by the senminum virus 40 promoter; plasmid phRL-TK, which carries the gene for Renilla luciferase; and plasmid pGL3-basic, which carries the gene for firefly luciferase were purchased from Promega (Madison, WI).…”
Section: Viral Vectorsmentioning
confidence: 99%
“…and is a function of E1A. A limited number of cellular genes undergo negative regulation by E1A, including genes encoding two surface receptors, neu and HER2 (62), major histocompatibility complex class I (MHC-I) genes (31), and some differentiation genes (4). MHC-I downregulation is mediated only by the Ad12 E1A (a member of adenovirus subgroup A) and not Ad5 E1A (subgroup C).…”
Section: Discussionmentioning
confidence: 99%